Dirty Futures: Or How I Learned to Stop Worrying and Love Mother Nature. (4th April 2013) - Ward, Geoff; Titman, Mark
Abstract Not only do bacterial cells in the human body outnumber human cells, but human habitation leaves microbial traces in the air and on surfaces. With these facts in mind, architect and academic Geoff Ward re‐examines recent perceptions of 'the dirty' and recasts the natural in architecture in relation to it.